The Relationship of Noise Exposure to Job Stress in Sand Mining Workers in The Banjarbaru City Area - Puspita, Luna Yussy; Arifin, Arifin; Junaidi, Junaidi; Ali As, Zulfikar (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Noise is the sound of an inappropriate place and time. Workplace noise problems are a source of stress that causes psychological imbalances. Sources of noise in the workplace come from operating machines, such as sand mines in Cempaka and Banjarbaru, which contribute to workplace noise. Sand mines use diesel engines; the engine sound is loud enough that all workers in the mine are exposed to the noise. Workers who are exposed to high-intensity noise experience work stress. The study aimed to determine the relationship between noise exposure and work stress among sand mining workers in Banjarbaru. This observational-analytic study used a cross-sectional design. Observations were made on 25 workers who were exposed to noise. The data were analyzed using the Pearson correlation test. The results of noise measurements in sand mines ranged from 72.1 dBA to 88 dBA, with noise exposure for each worker ranging from 65.5 dBA to 83.7 dBA and work stress scores ranging from 34.12% to 50.7%. Statistically, there is an association between noise exposure and work stress. It is recommended to check the diesel engine, lubricate it to reduce noise in old and poorly maintained engines, use ear protection devices, such as ear plugs and ear muffs, to reduce noise exposure, and rotate every job task, especially for workers around diesel engines.